From film practice to data process : production aesthetics and representational practices of a film industry in transition - Atkinson, Sarah, 1975- (Edinburgh University Press, 2018)
With an in-depth case study of Sally Potter's 2012 film Ginger & Rosa, and drawing upon interviews with international film industry practitioners, From Film Practice to Data Process is a groundbreaking examination of film production in its totality, in a moment of profound change.